Influence of vitamin E supplementation and basal diet on the vitamin E status, performance and tissue fatty acid concentration in lambs - E. Kasapidou; M. Enser; J.D. Wood; R.I. Richardson; R.G. Wilkinson; L.A. Sinclair (Animal, 2009)
In order to determine the effect of dietary vitamin E level and basal diet on vitamin E status, performance and tissue fatty acid content, five groups of eight Suffolk × Charollais wether lambs with an initial live weight of 28.4 (s.d. 1.6) kg were allocated to one of five concentrate-based diets supplemented with all-rac-α-tocopheryl acetate to contain 30 mg (C-30), 60 mg (C-60), 120 mg (C-120), 250 mg (C-250) or 500 mg (C-500) α-tocopheryl acetate/kg dry matter (DM), for 63 days. Two additional groups of eight lambs entered the study at 31.2 (s.d. 3.3) kg and were fed grass silage and 400 g/day concentrate for 56 days, with the whole diet providing the equivalent of 60 mg (S-60) or 500 mg (S-500) α-tocopheryl acetate/kg DM. Lambs were weighed and blood samples obtained by venipuncture weekly. Dietary vitamin E level did not affect performance (P > 0.05), but lambs fed grass silage grew more slowly (P < 0.001) and had a higher (P < 0.001) feed conversion ratio (kg feed/kg gain) than those fed concentrates. At day 0 plasma α-tocopherol concentrations were 0.8 μg/ml and did not differ between treatments (P > 0.05). Plasma α-tocopherol concentrations then decreased in all lambs except for those fed S-500, which increased, and at slaughter were (μg/ml) 0.07, 0.23, 0.39, 0.76 and 1.57 in C-30, C-60, C-120, C-250 and C-500 and 1.18 and 1.93 in S-60 and S-500, respectively. At slaughter, muscle and liver α-tocopherol concentrations were in the deficiency range for lambs fed C-30, C-60 or C-120, whereas plasma creatine kinase and tissue polyunsaturated fatty acids were unaffected by dietary vitamin E level, but creatine kinase levels were higher (P < 0.05) and glutathione peroxidise levels lower (P < 0.001) in lambs fed grass silage than concentrates alone. Muscle and liver α-tocopherol concentrations were 1.8- and 4.1-fold higher in lambs fed S-60 than C-60, but there was less of a difference between lambs fed S-500 or C-500 with muscle and liver differences of 0.4- and 0.7-fold, respectively. Tissue n-3 polyunsaturated fatty acid concentrations were higher (P < 0.05) and n-6 fatty acids lower in lambs receiving the grass silage compared to concentrate-based diets, but were not affected by dietary vitamin E level. It is concluded that lower plasma and tissue levels of α-tocopherol are present in lambs supplemented with all-rac-α-tocopheryl acetate on a concentrate compared to a mixed diet of silage and concentrates, and that normal growth can be achieved at tissue levels previously considered to represent deficiency.